2006
DOI: 10.1002/ar.a.20393
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF and pleiotrophin in deer antler

Abstract: Deer antlers represent a unique model of mammalian regeneration in that they cast and fully regenerate every year. The deer antler thus provides a fascinating model of both rapid angiogenesis and chondrogenesis and the opportunity to investigate unique growth regulatory processes. One such phenomenon is the presence of vascularized cartilage in the growing antler tip-unlike other cartilage, which is typically avascular. The mechanisms by which blood vessels grow in the cartilage as well as the factors that dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…These results are consistent with the reports that precartilage region in antler tip is characterized by impressively proliferation of the vascular associated cells [4], and is likely to contain factors that specifically regulate the growth of blood vessels. Additionally, pleiotrophin [5], an angiogenic factor, was found in this study, which might contribute to the promoting effect on proliferation of HUVEC.…”
Section: Effects Of Sequential Fractions From Antler Growing Tips On supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the reports that precartilage region in antler tip is characterized by impressively proliferation of the vascular associated cells [4], and is likely to contain factors that specifically regulate the growth of blood vessels. Additionally, pleiotrophin [5], an angiogenic factor, was found in this study, which might contribute to the promoting effect on proliferation of HUVEC.…”
Section: Effects Of Sequential Fractions From Antler Growing Tips On supporting
confidence: 93%
“…Therefore, antlers are considered as valuable models for studying the signaling pathways which modulates the development of these tissues. Recent evidence suggests that antler regeneration is a stem cell-based process, and some growth factors, such as VEGF, EGF, FGF and NGF, have been proved to be involved in the exceptional growth [4][5][6][7], in which some undiscovered modulating factors with low abundance or short-half-life in development of normal tissues may be over-expressed and more likely be found. Thus, investigation on the activities of proteins extracted from velvet antlers might lead to the founding of new active factors which play roles in the development of tissues mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Clark et al [4] reported presence of pleiotropin mRNA both in the antler tip and in its velvet dermis. Pleiotropin is considered a strong angiogenic factor [9] and might explain the abundant dermal irrigation we are reporting.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the cascade of events leading to rapid growth and osteogenic activity, current research has focused on identifying and characterizing trophic factors present in the regeneration phase of this organ. Besides, the effects of hormones, growth factors such as insulin-like growth factor, epidermal growth factor, vascular endothelial growth factor, nerve growth factor, as well as bone morphogenetic proteins, have been shown to play important roles in regeneration processes of deer antler [1,4,10,15,17].…”
Section: Discussionmentioning
confidence: 99%